Prediction and Outcome of Intensive Care Unit-Acquired Paresis. (January 2018) - Peñuelas, Oscar; Muriel, Alfonso; Frutos-Vivar, Fernando; Fan, Eddy; Raymondos, Konstantinos; Rios, Fernando; Nin, Nicolás; Thille, Arnaud W.; González, Marco; Villagomez, Asisclo J.; Davies, Andrew R.; Du, Bin; et al.
Background: Intensive care unit-acquired paresis (ICUAP) is associated with poor outcomes. Our objective was to evaluate predictors for ICUAP and the short-term outcomes associated with this condition. Methods: A secondary analysis of a prospective study including 4157 mechanically ventilated adults in 494 intensive care units from 39 countries. After sedative interruption, patients were screened for ICUAP daily, which was defined as the presence of symmetric and flaccid quadriparesis associated with decreased or absent deep tendon reflexes. A multinomial logistic regression was used to create a predictive model for ICUAP. Propensity score matching was used to estimate the relationship between ICUAP and short-term outcomes (ie, weaning failure and intensive care unit [ICU] mortality). Results: Overall, 114 (3%) patients had ICUAP. Variables associated with ICUAP were duration of mechanical ventilation (relative risk ratio [RRR] per day, 1.10; 95% confidence interval [CI] 1.08-1.12), steroid therapy (RRR 1.8; 95% CI, 1.2-2.8), insulin therapy (RRR 1.8; 95% CI 1.2-2.7), sepsis (RRR 1.9; 95% CI: 1.2 to 2.9), acute renal failure (RRR 2.2; 95% CI 1.5-3.3), and hematological failure (RRR 1.9; 95% CI: 1.2-2.9). Coefficients were used to generate a weighted scoring system to predict ICUAP. ICUAP was significantly associated with both weaning failure (paired rate difference of 22.1%; 95% CI 9.8-31.6%) and ICU mortality (paired rate difference 10.5%; 95% CI 0.1-24.0%). Conclusions: Intensive care unit-acquired paresis is relatively uncommon but is significantly associated with weaning failure and ICU mortality. We constructed a weighted scoring system, with good discrimination, to predict ICUAP in mechanically ventilated patients at the time of awakening.